Early Phase Pediatric Cancer Trials: Progress Highlights Challenges. (16th January 2020) - Adamson, Peter C.
Abstract : This commentary focuses on the promise of more effective and less toxic treatments for children with cancer in the age of targeted therapy, as well as the challenges still to be overcome to best inform pediatric drug development.